Filsafat Pendidikan Ki Hajar Dewantara sebagai Landasan Pendidik di Era Digital - Sulistyaningrum, Fitri; Radiana, Usman; Ratnawati, RR. Eka (LP. Ma'arif Janggan Magetan, 2023)
This research aims to analyze the relevance and applicability of Ki Hajar Dewantara's educational philosophy in facing the increasingly developing digital era. Ki Hajar Dewantara, as an Indonesian education figure, has rich and deep pedagogical principles. However, in facing significant challenges and changes in the world of education caused by digital technology, the relevance of this traditional approach needs to be evaluated. This article examines Ki Hajar Dewantara's educational principles, such as